Perilaku Konsumen Muslim Dalam Pengambilan Keputusan Pembelian Produk Makanan Impor - Elva Lativia; Tuti Kurnia; Wildan Munawar (Jurnal Iqtisaduna, 2022)
This study aims to determine the behavior of seasonal consumers in making purchasing decisions for imported food products. The research method used is quantitative with a descriptive approach using logistic regression analysis techniques. The population of this study is the Muslim community of Bogor City with a sample of 120 respondents. The types of data used are primary data and secondary data. The data collection technique used a questionnaire distribution technique. Based on the results of descriptive analysis, the characteristics of consumers who purchase imported packaged food products are the Muslim community of Bogor City, who have an age range of 21-30 years. Consumers really prioritize halal labels in making decisions. It also involves religious considerations before buying imported food products. Consumers are also actively using social media and have an interest in cultures that come from abroad. Based on the results of logistic regression analysis that examines the behavior of Muslim consumers in Bogor City using the variables of halal label, religiosity, lifestyle and product knowledge on purchasing decisions, it shows that halal labels and religiosity have a partial effect on purchasing decisions. Meanwhile, the halal label, religiosity, lifestyle and product knowledge simultaneously affect purchasing decisions.